Criminal Law Enforcement Corruption Against State-Owned Enterprises After The Enactment of The SOE Law In 2025 - Loren, Medina; Prasetyo, Handoyo (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: State-Owned Enterprises (SOEs) play a strategic role in Indonesia’s welfare-state framework but remain highly vulnerable to corruption, particularly due to long-standing ambiguities in the legal status of SOE assets. Specific Background: The enactment of Law No. 1 of 2025 and Law No. 16 of 2025 fundamentally redefines SOEs as pure corporate entities by separating SOE assets from state finances and adopting the Business Judgment Rule (BJR). Knowledge Gap: Despite these reforms, there is limited scholarly clarity on how corruption law enforcement should be applied to SOEs after 2025, especially in distinguishing business risk from criminal abuse of authority. Aims: This study analyzes the direction and implications of corruption law enforcement against SOEs following the 2025 SOE Law. Results: Using a normative legal method and case-based analysis of the LPEI, PT BRI, and PT Perindo cases, the study finds that SOE accountability may shift to the public domain when losses arise from conflicts of interest or abuse of authority, thereby nullifying BJR protection. Novelty: This research is among the first to systematically examine corruption enforcement under the post-2025 SOE legal regime using recent cases. Implications: The findings emphasize the need for clear enforcement guidelines to prevent the misuse of BJR while ensuring legal certainty and effective anti-corruption measures in SOEs. Highlights: Asset Separation: SOE assets are legally distinguished from state finances, altering the basis for determining public financial loss. BJR Limitation: The Business Judgment Rule protects good-faith decisions but does not apply where conflicts of interest or abuse of authority exist. Enforcement Direction: Corruption law remains applicable to SOEs when corporate governance failures shift accountability to the public domain. Keywords: State-Owned Enterprises, Corruption Law Enforcement, Business Judgment Rule, Corporate Accountability, Legal Reform